Three Dimensional Analysis on Stress Concentration in a Gas Turbine Blade - Nur Hazwana binti Kabol, Nur Hazwana (Universiti Teknologi Petronas, 2010)
Gas turbine works under high stress and high temperature. The stress is distributed over the whole turbine blade when it is operating in the jet engine. The presence of fillets and sharp edges in the profile of gas turbine blade localizes some of the stresses which is called as stress concentration. If the material unable to withstand the stresses subjected on it which are centrifugal force of 16.58 kN and fluid pressure difference of 1596.4 kN, fracture is highly happened. This project studies about the stress being concentrated within the turbine blade.